Role of corrosion in taper failure and head disassociation in total hip arthroplasty of a single design - Martin, Audrey J.; Jenkins, Derek R.; Van Citters, Douglas W. (Journal of orthopaedic research, 2018)
ABSTRACT Modular junctions have been associated with corrosion in total hip arthroplasty. In a small number of cases, disassociation of the femoral head from the stem following gross wear of the taper has been reported. The purpose of this study was to investigate the role of corrosion in the development of mechanical changes leading to disassociation. Twenty‐one retrieved stems and heads of one design previously reported with head disassociation were identified in an IRB‐approved database. Components were scored for corrosion and measured for material loss. Stem alloy hardness was measured. Parametric and non‐parametric statistics were performed (α < 0.05). Seven of twenty‐one stems demonstrated gross material loss of the stem taper and head disassociation. The maximum linear depth (MLD) of material loss on stem tapers without dissociation and all head bores was 7.63 ± 6.04 and 63.76 ± 60.83 μm, respectively. Hardness of the stem material was statistically distinct, but similar to other stem materials. Results suggest material loss via corrosion at the head bore loosens the taper lock, allowing relative motion leading to abrasive wear of the stem taper. All cases of disassociation occurred at greater than 65 months with a minimum of 50 μm of loss at on the head bore. It may be warranted to survey patients with systems reporting head disassociation; for this system, including recalled heads, risk appears to begin after 6 years in vivo. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2996–3003, 2018.